GAMBARAN POTENSI INTERAKSI OBAT HIPERTENSI DI INSTALASI FARMASI RAWAT JALAN RUMAH SAKIT METROPOLITAN MEDICAL CENTRE PERIODE OKTOBER – DESEMBER 2018 - Honey Iskandar; Dessy Adelia; Anissa Muharomah (Jurnal Farmasi IKIFA, 2021)
According to the American Heart Association (AHA), Americans over the age of 20 suffer from hypertension, reaching up to 74.5 million. Based on data from the Health Research (RISKEDAS) 2013, the prevalence of hypertension in Indonesia is 25.8%. Hypertension is a silent killer where symptoms can vary in each individual. Hypertension is one of the main risk factors for heart disease, stroke, visual impairment and kidney disease. So in the treatment of hypertension the possibility of polypharmacy so that the occurrence of drug interactions increases. Drug interaction is a modification of the effect of a drug due to other drugs given initially or given together so that the effectiveness or toxicity of one drug or more changes. Based on data obtained from the medical record of Metropolitan Medical Center Hospital for primary hypertension in outpatient Metropolitan Medical Center Hospital in the period July to December 2018 there were 441 visits and ranked number 3. This study aims to determine the potential for drug interactions and determine the percentage of potential drug interactions based on the severity of drug interactions at the Metropolitan Medical Center Hospital Outpatient Pharmacy Installation from October to December 2018 using drugs.com software. This research is a descriptive study and is included in a retrospective type of evaluative research. The number of samples taken was 322 prescription sheets with the taking technique used, namely the purposive sampling method. The results showed that there were 216 prescription sheets (67.08%) that had drug interactions with interaction severity ie minor (12.67%), moderate (78.73%), and major (8.60%).